Hubungan Pengetahuan Dismenore Dan Perilaku Makan Terhadap Kejadian Dismenore Pada Remaja Putri Di SMA Negeri 1 Pulau Banyak Kabupaten Aceh Singkil Tahun 2024 - PUTRI, YOLANDA; Febriansyah, M. Irfan; Wahyuni Muhsin, Sri; Masitah, Ravi (Jurnal Biogenerasi, 2025)
Adolescence is a critical developmental period marked by hormonal changes, including the onset of menstruation. Dysmenorrhea is a common complaint among adolescent girls and may be influenced by knowledge and dietary behavior. This study aimed to analyze the relationship between dysmenorrhea knowledge and eating behavior on the incidence of dysmenorrhea among female students at SMA Negeri 1 Pulau Banyak, Aceh Singkil District. This research employed a quantitative method with a cross-sectional design. The sample consisted of 77 students selected using total sampling. Data were collected using questionnaires and analyzed with the Chi-Square test. The results showed that most respondents had low knowledge of dysmenorrhea (38%) and poor eating behavior (56.5%). The majority experienced severe dysmenorrhea (78.3%). Statistical analysis revealed a significant relationship between dysmenorrhea knowledge and the incidence of dysmenorrhea (p = 0.000) and between eating behavior and dysmenorrhea incidence (p = 0.000). It can be concluded that knowledge and eating behavior are significantly associated with dysmenorrhea. Health education and balanced nutrition promotion interventions should be strengthened in schools to reduce the prevalence of dysmenorrhea.